Digitalization of the Russian Energy Sector: State-of-the-art and Potential for Future Research - Alekseev, Alexander N.; Lobova, Svetlana V.; Bogoviz, Aleksei V.; Ragulina, Yulia V. (International Journal of Energy Economics and Policy, 2019)
In this paper, we review forty seven best papers on digitalization of the Russian fuel and energy complex. All the papers are written in Russian and published in a number of Russian academic journals that are mostly distributed via closed national library systems and, consequently, are not available for foreign scholars interested in studying Russia’s energy policies. Our review identifies a total of five research directions in the Russian scholarship: (i) general trends in digitalization of the Russian fuel and energy complex; (ii) concepts and approaches used by the Russian scholars; (iii) government policies; (iv) digital technologies; and (v) security concerns. Each research direction is carefully covered and analyzed. Then, we identify gaps in the Russian scholarship and propose three potential research areas. Keywords: Digitalization, Energy Industries, Russia, Contemporary Scholarship JEL Classifications: Q2, Q3, Q4 DOI: https://doi.org/10.32479/ijeep.7673